Gambaran Nilai Ct Value qRT-Pcr Sars Cov-2 Dengan Metode Ekstraksi Manual Dan Otomatis - Antik Murwani; Muhammad Taufiq Qurrohman (Universitas Muhammadiyah Surabaya, 2023)
Corona Virus Infection Disease (COVID)-19 is a disease caused by a new coronavirus C derivative. The SARS-CoV-2 genome has six main open reading frames (ORFs): ORF 1a and 1b, envelope protein/E genes, membrane protein/M genes, spike protein/S gene, and nucleocapsid protein/N genes.Â Realtime RT-PCR is a DNA amplification technique in which amplification products can be analyzed at each cycle using fluorogenic probes.Â The RT-PCR method is used for amplification, isolation, or identification of sequences from RNA cells or tissues. The extraction of nucleic acids in the form of DNA and RNA is the initial process for biomolecular studies. The principle in the extraction of genetic material in the form of DNA and RNA is to break down cells and genetic material in the cell from other cellular components in the form of fats, proteins, carbohydrates, and other substances. The purpose of this study is to find out the picture of the value of CT Value qRT-PCR SARS-CoV-2 using two extraction methods, namely manual and automatic. This study was descriptive using accidental sampling techniques of positive patients confirmed with COVID-19. Swab samples are carried out using manual and automatic extraction methods, then qRT-PCR examination is carried out. The results of descriptive statistical tests obtained the Mean Gene E value of manual extraction 19.1290 and automatic extraction 18.8187, as well as the Mean Gene value of ORF1ab manual extraction 19.1290 and automatic extraction 19.5177.